Autonomic dysfunction in a patient with primary headache associated with sexual activity: case report and literature review - Yimo Zhang; Hairong Qian; Shengyuan Yu (BMC Neurology)
Abstract Background Primary headache associate with sexual activity (PHASA) is a relatively rare clinical condition and characterized by thunderclap headache exclusively triggered by sexual activity. The suggested involvement of autonomic dysfunction with altered cerebrovascular tone may contribute to the underlying mechanism of PHASA. However, the utilization of head-up tilt test (HUT), a valuable tool for assessing autonomic function, has not been employed in patients with PHASA. Case presentation We present a typical case of PHASA with positive HUT response. Conclusion Autonomic dysfunction and compensatory vasodilation due to cerebrovascular autoregulation may be part of the mechanism of PHASA.